Elimination of soluble 123I-labelled aggregates of human immunoglobulin G in humans; the effect of splenectomy. - Halma, C (1989)
To study the role of the spleen in the elimination of immune complexes we examined mononuclear phagocyte system function in eight healthy controls and eight splenectomized patients, with soluble 123I-labelled aggregates of human immunoglobulin G (AIgG). No differences were found between the two groups in elimination and degradation of AIgG. The loss of splenic function was compensated for by increased uptake of AIgG by the liver. With the dose of 123I-AIgG used in this study (10 micrograms/kg body weight), significant generation of C3a was observed. No correlation was found between erythrocyte CR1 number and the fraction of aggregates that bound to erythrocytes.